Multimetallic permethylpentalene hydride complexes - Fraser, DAX; Turner, ZR; Cooper, RT; Buffet, J-C; Green, JC; O'Hare, D (American Chemical Society, 2022)
The synthesis and characterization of group 4 permethylpentalene (Pn* = C8Me6) hydride complexes are explored; in all cases, multimetallic hydride clusters were obtained. Group 4 lithium metal hydride clusters were obtained when reacting the metal dihalides with hydride transfer reagents such as LiAlH4, and these species featured an unusual hexagonal bipyramidal structural motif. Only the zirconium analogue was found to undergo hydride exchange in the presence of deuterium. In contrast, a trimetallic titanium hydride cluster was isolated on reaction of the titanium dialkyl with hydrogen. This diamagnetic, mixed valence species was characterized in the solid state, as well as by solution electron paramagnetic resonance and nuclear magnetic resonance spectroscopy. The structure was further probed and corroborated by density functional theory calculations, which illustrated the formation of a metal-cluster bonding orbital responsible for the diamagnetism of the complex. These permethylpentalene hydride complexes have divergent structural motifs and reactivity in comparison with related classical cyclopentadienyl analogues.